2015
DOI: 10.1063/1.4931807
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the isothermal crystallization of the mono-alcohol n-butanol monitored by dielectric spectroscopy

Abstract: Isothermal crystallization of the mono-hydroxyl alcohol n-butanol was studied with dielectric spectroscopy in real time. The crystallization was carried out using two different sample cells at 15 temperatures between 120 K and 134 K. For all temperatures, a shift in relaxation times to shorter times was observed during the crystallization process, which is characterized by a drop in relaxation strength. The two different sample environments induced quite different crystallization behaviors, consistent and repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
1
17
1
Order By: Relevance
“…This result can now be understood as coming from the partial ordering of the LC. The recently reported disappearance of the Debye process combined with the survival of the liquid-like β-process 26 during the transition is similarly fully consistent with the breakup of the hydrogen-bonded clusters in the isotropic liquid and formation of the LC.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result can now be understood as coming from the partial ordering of the LC. The recently reported disappearance of the Debye process combined with the survival of the liquid-like β-process 26 during the transition is similarly fully consistent with the breakup of the hydrogen-bonded clusters in the isotropic liquid and formation of the LC.…”
Section: Discussionsupporting
confidence: 80%
“…The Raman spectrum of isotropic liquid in the OH-stretch region is very broad corresponding to the formation of 1 to 3 hydrogen bonds 23 and broadening caused by orientational disorder. Based on computer simulations of n -octanol 24 , small-angle x-ray scattering studies of n -alcohols 25 , and dielectric-relaxation studies 26 , it can be concluded that the isotropic liquid forms clusters with a polar hydrogen-bonded core and a nonpolar shell consisting of overlapping alkyl chains (see Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference was mainly due to the geometry of the container used in both experiments, as it is one of the factors affecting the beginning and progress of the crystallization process. 46 In the third step, the equilibrium concentration of the drug remaining in the polymer matrix after annealing is determined. This is done by determining the glass-transition temperature of the annealed material by DSC/BDS.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…This difference was mainly due to the geometry of the container used in both experiments, as it is one of the factors affecting the beginning and progress of the crystallization process. 46 …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation